Correlation Between Perceptions of Family Health Services and Monitoring Growth Visits of Toddlers in The Working Area of Kaliwates Health Center Jember Regency - Sholeh, Mochammad Fikris; Susanto, Tantut; Kurdi, Fahruddin (Al-Hijrah Indonesia, 2023)
Perceptions of family health services are associated with visits to monitor toddlers' growth. Poor perceptions of family health services can be at risk of reducing monitoring visits and the growth of toddlers. This study aims to analyze the correlation between the perception of family health services and the visits for growth monitoring of Toddlers in the working area of Kaliwates Community Health Center in Jember Regency. The research design used an observational correlational study. The sampling technique used in this research was Consecutive Sampling with 70 respondents from families with Toddlers. A questionnaire on family health service perception (ServQual) was used to assess the perception of family health services. A questionnaire on Toddlers' growth monitoring visits (PIS-PK) was used to measure whether or not Toddlers underwent growth monitoring visits. The chi-square test analysis showed a p-value of <0.001 (p < 0.05), indicating a significant correlation between the perception of family health services and Toddlers' growth monitoring visits. Most respondents had a positive perception, with 47 respondents (67.1%) having a good perception. Most Toddlers' growth monitoring visits were also good, with 44 respondents (62.9%) having undergone regular monitoring. Therefore, it is essential to establish a good perception of family health services to maintain and enhance the visits for Toddlers' growth monitoring